2018
DOI: 10.13189/ujer.2018.060616
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Passion, Perfectionism and Burnout in Athletes

Abstract: This study was carried out with the goal of examining the relationship between athletes' passion and perfectionism levels and athlete burnout, and to determine to what extent passion and perfectionism scores predict burnout experienced by athletes. A total of 267 athletes, located in various parts of Turkey and competing in various branches of sport, participated in the study on a voluntary basis. Of the participants, 65 were women (mean age: 20.12 ± 3.68 years) and 202 were men (mean age: 20.2 ± 4.04 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Contrary to this finding, Kuan-Yu, Ching-Wen & Cheng-Hua (2019) showed that obsessive passion had a significant positive effect on emotional exhaustion. Demirci & Çepikkurt (2018) also reported a meaningful positive relationship between obsessive passion and emotional exhaustion as one of the components of burnout. This difference in the findings of the present study with the results of Kuan-Yu, Ching-Wen & Cheng-Hua (2019), Demirci & Çepikkurt (2018), and Gustafsson & Hassmen (2011) are probably due to differences in some of the features of the research sample, and it seems that the sport environment and their viewpoints are different from those of the student athletes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to this finding, Kuan-Yu, Ching-Wen & Cheng-Hua (2019) showed that obsessive passion had a significant positive effect on emotional exhaustion. Demirci & Çepikkurt (2018) also reported a meaningful positive relationship between obsessive passion and emotional exhaustion as one of the components of burnout. This difference in the findings of the present study with the results of Kuan-Yu, Ching-Wen & Cheng-Hua (2019), Demirci & Çepikkurt (2018), and Gustafsson & Hassmen (2011) are probably due to differences in some of the features of the research sample, and it seems that the sport environment and their viewpoints are different from those of the student athletes.…”
Section: Discussionmentioning
confidence: 91%
“…Results showed that the harmonious passion had a significant negative effect on emotional exhaustion, while obsessive passion had a significant positive effect on emotional exhaustion. By examining the relationship between passion and burnout among athletes, Demirci & Çepikkurt (2018) showed that there is a positive relationship between obsessive passion and emotional burnout as one of the components of burnout. But there is a meaningful negative relationship between harmonious passion and worthlessness.…”
Section: Introductionmentioning
confidence: 99%
“…According to findings by Vallerand [17] regarding the sport performance and motivation, it has been shown that negative affect predicts athlete's burnout [27]. Burnout can lead to several problems including decrease in performance, feeling frustrated, unmotivated, exhausted, and sometimes depress [28].…”
Section: Passion In Athletesmentioning
confidence: 99%
“…It has recently been observed that the concept of passion is investigated especially in the perspectives of sports and physical activity (Bayköse et al, 2017;Demirci & Çepikkurt, 2018, Kelecek & Aşçı, 2018. By increasing the importance and participation of individuals in physical activity, their tendency towards physical activity and their attachment began to be researched.…”
Section: Introductionmentioning
confidence: 99%